INTENSITY OF PHYTONEMATODES IN CITRUS ORCHARDS OF NORTH WEST FRONTIER PR OVINCE AND THEIR CONTR OL THROUG H INDIG ENOUS NEMATICIDES: Short Communication (Biological Sciences - PJSIR, 2002)
Among several other pests attacking citrus plants, citrus nematodes Ty lenchulus semipene trans is one of the important pests widely spread in all the citrus growing areas of the country responsible for the citrus decline. It incurred damages to citrus industry to the extent of 60- 80% in a country like United States. The losses in Pakistan and other developing countries may be far greater. Heavy population of plant parasitic  nematodes were recovered in association with citrus roots and its rhizophere in Punjab (Anwar and Sanvar 1981). In Pakistan the causal agent of citrus decline has been reported from all the four provinces by Brown (1962). Recently a survey of citrus growing areas in NWFP & Taxila (Punjab) was conducted to evaluate the nematode fauna and their intensity around the roots vicinity of citrus trees. Hoplolaimus columbus, Hoplolaimus par arobustus, H indicus, Helicotylenchus multicinctus, H indicus, Tylenchus semipen etrans and Aphelen chus avenae were found to be attacking the roots of citrus plants (Calabratta 1995; Elekcioghu 1995) as pre sented in Table 1.